Efficient and oriented oxidation of all n-alkanes in soil by direct passivation of soil organic matter - Xu, Jinlan; Wang, Manman; Li, Huan; Gao, Mengzhen; Liu, Chuanyu; Dai, Jianan; Cao, Zezhuang; Guan, Huiwen (Journal of environmental chemical engineering, 2025)
To explore the influence of soil organic matter on the degradation of all n-alkanes (C10-C30) in soil, it is proposed to regulate organic matter by kaolin and then perform Fenton oxidation to repair petroleum-contaminated soil. The results show that due to the protonation of functional groups, the content of protein and humus in soil is greatly reduced by the adsorption of kaolin. After the addition of kaolin, the total petroleum hydrocarbons (TPH) oxidation of the high-efficiency group was up to 7372 mg/kg, which was 1.93 times that of the unregulated group. Among them, the oriented oxidation amount of TPH in the high-efficiency group was 3555 mg/kg, and the remediation efficiency was 19.71 % higher than that in the unregulated group, realizing the oriented oxidation of all n-alkanes in the soil. Further analysis found that the direct passivation of soil organic matter is mainly through the deprotonation of hydroxyl on the surface of kaolin minerals and combined with carboxyl groups, hydroxyl groups, and other functional groups of organic matter. Therefore, kaolin can absorb some small molecules in organic matter (protein II, humic acid, fulvic acid), which can directly passivate organic molecules and weaken the capture ability of organic matter to •OH. This greatly reduces the ineffective consumption of •OH by SOM（soil organic matter） and increases the utilization rate of H2O2, which provides a great reference value for practical engineering applications. [Display omitted] •SOM molecules were directly passivated by kaolin.TPH oxidation was higher (7372 mg/kg) in the high-efficiency group, which was 1.93 times that in the unregulated group.•Due to protonation, C-O and alcohol or phenol O-H are adsorbed, which leads to transfers of more ·OH to TPH and improves the reactivity of ·OH with TPH.•After soil regulation, the reactivity coefficient of ·OH and TPH enhanced from 0.35 to 1.91, which was conducive to the efficient oriented oxidation of all n-alkanes.